Clinical Characteristics and Risk Factors for the Recurrence of Benign Paroxysmal Positional Vertigo - Zhu, Cui Ting; Zhao, Xing Qquan; Ju, Yi; Wang, Yan; Chen, Mei Mei; Cui, Yu (Frontiers in Neurology, 2019)
Abstract Benign Paroxysmal Positional Vertigo (BPPV) manifests itself as a paroxysm of vertigo and nystagmus lasting several seconds, which is self-limiting. The clinical characteristics and risk factors for the recurrence of BPPV in different ages have not yet been investigated. Materials and methods: A retrospective observational study was conducted in the department of Neurology in Beijing Tiantan Hospital from July 2009 to June 2015. The study included 1012 patients aged 18 to 93 years old. All patients received the definitive diagnosis and canalith repositioning maneuvers treatment and finally accomplished follow-up. Demographic variables, potential recurrence risk factors, neurological examination, and laboratory indexes were assessed. Data Analyses: The t test or Chi-squared test was firstly performed for group comparison, then Logistic regression analysis was used to investigate the risk factors of BPPV recurrence. Results: The one year recurrence rate of BPPV patients after reposition maneuvers was respectively 22.79%(aged 18 to 45 years), 23.92%(aged 45 to 60 years), 28.89%(over 60 years). The recurrence rate between three groups has no statistical significance. Logistic regression analysis shows that women BPPV patients have more recurrence risk than men. Meniere’s disease (odds ratio = 6.009, 95% confidence interval: 2.489-14.507, p < 0.001), hypertension (odds ratio = 1.510, 95% confidence interval: 1.095-2.084, p = 0.012), migraine (odds ratio = 2.534, 95% confidence interval: 1.164-5.516, p = 0.019), and hyperlipemia (odds ratio = 1.419, 95% confidence interval: 1.024-1.968, p = 0.036) were risk factors for the recurrence of BPPV patients. Conclusion: We conclude that Meniere’s disease, hypertension, migraine, and hyperlipemia may be independent risk factors for the recurrence of BPPV patients, but aging does not increase the recurrence risk.